Merely a transitory evil: the diplomatic benefits of Italian military defeats from 1896 to 1918 - Innocenti, Claudio Roberto (Kansas State University, 2024)
This dissertation counters the general perception of Italian military ineffectiveness in the 19th and 20th centuries to argue in favor of the political values of military disasters. Major defeats at Adwa in 1896 and Caporetto in 1917 enabled the Kingdom of Italy to gain more political leverage over both allies and rivals in a way that was not possible before those failures. In particular, a special relationship with Great Britain provided the opportunity for Italian politicians to manipulate stronger states from a position of weakness. Thus, battlefield disasters provide the impetus for nations to embark on internal reforms and to secure international support to redress a state of temporary weakness.
Keywords: Italian military history; Strategic culture; Defeats